Biomechanical evaluation of various fixation strategies in oblique lumbar interbody fusion: a finite element analysis - Jinyue He; Jiezhong Deng; Yu Xiang; Yusheng Yang; Sheng Liao; Hui Chen; Fei Luo; Jianzhong Xu; Zhongrong Zhang; Zehua Zhang (BMC Musculoskeletal Disorders)
Abstract Background context Typical oblique lumbar interbody fusion (OLIF) generally employed either the single lateral screw (SLS) or dual pedicle screws (DPS) for instrumentation, each with their own limitations. Purpose The study aimed to investigate the biomechanical properties of two additional fixation strategies including single reverse pedicle screw (SRS) and dual overlapped screws (DOS) compared with SLS and DPS. Study design A finite element (FE) analysis study. Methods A L2-5 finite element model was established and validated with L4/5 as the experimental segment. Four fixations including SLS, SRS, DPS and DOS were established on the segment respectively. The L5’s inferior surface was set immobilized. Follower-loaded bending moments were imposed on the superior surface of L2 to record the segment’s range of motion (ROM) and maximum stress (MS) on the screws, cage and cortical bone under F-E (flexion and extension), bending (left and right) and rotation (left and right). Results The model was validated feasible through comparison with previous studies. Regarding the immediate stability: (i) the ROM was significantly lower in DPS and DOS compared to SLS and SRS during F-E and rotations; (ii) compared to DPS, DOS illustrated mildly increased ROM during F-E motions, and left rotation; (iii) compared to SLS, SRS showed an increase of ROM during flexion but a reduction in extension, without obvious distinctions during other motions. Regarding the mechanical response: (i) DPS and DOS illustrated lower MS on the screws, cortical bone and cage than SLS and SRS during most motions; (ii) Compared to DPS, DOS exhibited increased MS during most motions on the screws, cortical bone and cage; (iii) Compared to SLS, SRS demonstrated an increase of MS on the screws during flexion but an reduction during extension, along with decreased MS on cortical bone and cage during most motions. Conclusion Dual-screw systems (DPS and DOS) demonstrated enhanced immediate stability for the segment and mitigated mechanical loading for the instrument compared to single-screw systems (SLS and SRS); For the former, DOS exhibited comparable immediate stability to typical DPS, indicating the potential as a viable alternative; For the later, SRS manifested similar stability to traditional SLS, with less stress loading on the cage and cortical bone, indicating less risk of instrument failure in the long term. Clinical significance The study provides biomechanical references to achieve differentiated and individualized instrumentation for patients undergoing OLIF surgery.